Association of plasma ceramides with prevalent and incident type 2 diabetes mellitus in middle and older aged adults. (September 2021) - Dugani, Sagar B.; Christenson, Luke R.; Aakre, Jeremiah A.; Bui, Hai H.; Vella, Adrian; Mielke, Michelle M.
Abstract: Aims: The role of ceramides in the pathogenesis of type 2 diabetes mellitus (T2DM) is incompletely characterized. Given that ceramides represent therapeutic targets to disrupt the euglycemia-T2DM transition, we aimed to characterize their association with prevalent and incident T2DM in a novel cohort. Methods: We examined the cross-sectional and longitudinal association of baseline ceramides with prevalent and incident T2DM among 1423 adults (47% women; median (range) baseline age 72 (51–95) years) in the Mayo Clinic Study of Aging cohort. We examined the associations of ceramides with prevalent T2DM (adjusted odds ratio [95% confidence interval]) at baseline and incident T2DM (adjusted hazard ratio [95% confidence interval]) during median follow-up of 6.2 years, after adjusting for demographic and metabolic factors. Results: Among 1423 adults, there were 222 prevalent and 37 incident cases of T2DM. In cross-sectional analyses, higher levels of ceramide C16:0 were associated with lower odds of prevalent T2DM (aOR 0.84 [0.71–0.99]; P = 0.03) whereas C18:0 (aOR 1.27 [1.06–1.42]; P = 0.01), C18:0/16:0 (aOR 1.41 [1.22–1.62]; P < 0.001) and C18:0/24:0 (aOR 1.22 [1.05–1.41]; P = 0.01) were associated with higher odds. In Cox hazard regression models, C18:0/16:0 (aHR 1.63 [1.26–2.10]; P < 0.001) and C18:0 (aHR 1.53 [1.12–2.08]; P = 0.01) were associated with increased risk of incident T2DM. Conclusions: In this prospective population-based cohort, ceramides were associated with prevalent T2DM (C16:0, C18:0, C18:0/C16:0 ratio, C18:0/C24:0 ratio) and incident T2DM (C18:0, C18:0/C16:0 ratio) and could suggest targets for the primary and secondary prevention of T2DM.